2022
DOI: 10.55059/ijm.2022.1.2/23
|View full text |Cite
|
Sign up to set email alerts
|

Some new generalized Ostrowski type inequalities with new error bounds

Abstract: In this paper, we will ameliorate and generalize Ostrowski type inequality for twice differentiable mappings in various Lebesgue spaces. Some famous inequalities can be derived as a special cases of the inequalities obtained here. Furthermore, perturbed mid-point inequality and perturbed trapezoid inequality are also obtained. The obtained inequalities have very rapid applications in numerical integrations and some special means.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Finally, by using the functional properties of the abstract space, in which these derivatives belong to, these identities can be converted into Ostrowski's like inequalities. Some of these studies can be found in Alshanti, 2018Alshanti, , 2019Alshanti and Milovanovic, 2020;Alshanti, 2021;Amjad et al, 2022;Liu et al, 2016;Dragomir and Sofo, 2000;Liu and Park, 2017a;Liu and Lu, 2015;Liu and Park, 2017b;Al-Zoubi et al, 2019). Also, for more rigorous related approaches, we refer the reader to (Milovanović, 2017;Milovanović and Pečarić, 1976;Milovanović, 1975;Milovanovic, 1977;Vasić and Milovanović, 1976;Ðorđević and Milovanović, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, by using the functional properties of the abstract space, in which these derivatives belong to, these identities can be converted into Ostrowski's like inequalities. Some of these studies can be found in Alshanti, 2018Alshanti, , 2019Alshanti and Milovanovic, 2020;Alshanti, 2021;Amjad et al, 2022;Liu et al, 2016;Dragomir and Sofo, 2000;Liu and Park, 2017a;Liu and Lu, 2015;Liu and Park, 2017b;Al-Zoubi et al, 2019). Also, for more rigorous related approaches, we refer the reader to (Milovanović, 2017;Milovanović and Pečarić, 1976;Milovanović, 1975;Milovanovic, 1977;Vasić and Milovanović, 1976;Ðorđević and Milovanović, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Mappings play a vital role in the field of inequalities (see of example [17][18][19][20]). The mappings which have Lipschitzís constant equal to 1 are called as non-expansive mappings.…”
Section: Introductionmentioning
confidence: 99%
“…Some latest work done by S. Fahad et al [13]. Further works done by Iftikhar et al [14], Mustafa et al [15] and J. Amjad et al [16]. Let the functional S ( f ; ω; ȃ, ĉ) via weighted version represent the deviation of f ( ŝ) over [ ȃ, ĉ] defined as:…”
Section: Introductionmentioning
confidence: 99%